Cerebellar ataxia and autoantibodies restricted to glutamic acid decarboxylase 67 (GAD67) - Guasp, Mar (J Neuroimmunol, 2016)
Cerebellar ataxia is one of the most frequent syndromes associated with autoantibodies against glutamic acid de-carboxylase (GAD-ab). Antibodies recognize the isoform GAD65, which is the standard biomarker, but additional immunoreactivity against GAD67 is found in high proportion of patients with GAD-ab-associated neurological disorders. We describe the case of a 59-year-old woman who presented with pancerebellar syndrome of subacute onset (9 weeks to nadir). In the etiological study, high titers of GAD-ab were found, but these only recognized the GAD67 isoform and not the GAD65. Screening of GAD67-ab should be considered in late-onset cerebellar ataxia when GAD65-ab are absent.